Chemical composition, anti-inflammatory effect and antitumor activity of curly dock fruit (Rumex crispus L., Polygonaceae) - Samardžić, Stevan; Jakovljević, Dunja; Majkić, Tatjana; Beara, Ivana; Maksimović, Zoran; Ćebović, Tatjana (Archives of Pharmacy, 2022)
Curly dock (Rumex crispus L.) is a perennial herbaceous plant that is traditionally used in the treatment of gastrointestinal ailments, infections and skin diseases. The aim of this study was to examine the chemical composition, ex vivo anti-inflammatory effect and in vivo antiproliferative activity of water extract of curly dock fruit. The polyphenolic profile was analyzed by LC-DAD-ESI-MS technique. The effect on the production of arachidonic acid metabolites was examined in human platelets. Antitumor activity of orally administered extract (concentration: 5% w/v; doses: 1, 2 and 5 mL/kg of body weight/day; treatment length: 7 days) to Ehrlich ascites tumor and hepatocellular carcinoma was assessed in an animal experiment. Ascites volume, viable cell percentage and antioxidant enzyme levels were determined. The presence of phenolic acids (gallic and protocatechuic acids), proanthocyanidins (monomers, dimers and trimers), flavonoid glycosides and anthraquinone emodin was revealed in the water extract of R. crispus fruit. The content of the quantitatively dominant compound miquelianin was 2.4%. The investigated preparation concentration-dependently inhibited the synthesis of 12(S)-hydroxy-(5Z,8E,10E)-heptadecatrienoic acid (IC50 = 4.96 mg/mL) and 12(S)-hydroxy-(5Z,8Z,10E,14Z)-eicosatetraenoic acid (IC50 = 2.06 mg/mL). The antitumor effect in animals was dose-dependent and manifested as suppression of tumor growth and induction of cell death of malignantly transformed cells. Values ​​of biochemical parameters suggested that oxidative stress was induced in cancer cells, and it can be assumed that this mechanism was at least partly responsible for the activity. Water extract of R. crispus fruit has significant pharmacological potential that justifies further research.